(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The activities described were developed at the community level in the “Santa Rita” Popular Council to achieve a greater incorporation of older adults to the Senior Adult Chair, belonging to the Municipal University Center of Jiguaní and are based on the need to achieve from the university classrooms that these people have a happy old age and attribute to living 65 years or more its indisputable meaning from the university classrooms.